Analytical solution of VOCs emission from wet materials with variable thickness. (1st August 2016) - Deng, Baoqing; Zhang, Bing; Qiu, Yinfeng
Abstract: VOCs emission from wet materials leads to the movement of material-air interface with time. A transient diffusion equation with moving boundary is developed to describe VOCs emission from wet materials. A coordinate transform technique is presented to transfer the moving boundary problem into a fixed boundary problem. The generalized integral transform technique is used to obtain an analytical solution of the fixed boundary problem. An environmental chamber test on formaldehyde emission from oil-based paint is performed to validate the present model. Results of the present model agree well with the experimental data. The influence of parameters on the emission of formaldehyde is discussed. With the increase of diffusion coefficient, the VOCs emission rate increases. On the contrary, with the increase of partition coefficient, the VOCs emission rate decreases. The present model can be used to predict the emission of VOCs from wet coating materials with variable thickness. Highlights: Mathematical model for VOCs emission from wet materials is constructed. The coordinate transform technique is used to fix the boundary of wet materials. An analytical solution is obtained by using GITT.